Judicial Reasoning in Rendering Criminal Convictions Under Provisions Beyond the Public Prosecutor's Indictment in Narcotics Cases: A Juridical Analysis of the Supreme Court Decision No. 6087 K/Pid.Sus/2024 - Freshly Newman Silalahi; Ida Hanifah; Mhd. Teguh Syuhada Lubis (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study examines the juridical issue concerning the authority of judges to render criminal convictions by applying legal provisions that were not included in the public prosecutor’s indictment, particularly in narcotics-related criminal cases. Under the principle of litis contestatio, the indictment serves as a fundamental limitation on the scope of judicial examination and adjudication. However, in practice, the Supreme Court Decision No. 6087 K/Pid.Sus/2024 demonstrates a legal anomaly in which the panel of cassation judges found the defendant guilty under Article 127 Paragraph (1) Letter a of Law No. 35 of 2009 on Narcotics, despite the fact that this provision was not included in the prosecutor’s indictment, which was structured as a hierarchical subsidiary indictment under Articles 114 and 112 of the Narcotics Law. This normative legal research employs both a statutory approach and a case approach. The analysis reveals that convictions rendered beyond the scope of the indictment are inconsistent with the principle of legal certainty as embodied in Article 191 Paragraph (1) of the Indonesian Criminal Procedure Code (KUHAP) (or Article 244 Paragraph (2) of the New Criminal Procedure Code), under which the complete failure to prove the charges must result in an acquittal (vrijspraak). The legal implications of such deviation include the dysfunction of the indictment as a procedural instrument, the violation of the defendant’s right to defense, the potential abuse of judicial authority (ultra vires), and the erosion of public trust in the criminal justice system. The judges’ reasoning, which relied solely on the facts established during trial, disregarded both the attributed authority of the judiciary and the normative limitations imposed by criminal procedural law.